A pintura da Escola Nacional de Belas Artes na 1ª República (1890-1930): da formação do artista aos seus modos estilísticos - Valle, Arthur Gomes (2007)
The present work deals with the pictorial production of the artists of the Escola Nacional de Belas Artes (ENBA) of Rio de Janeiro in the period of the so-called Brazilian First Republic (1890-1930). Here, we approach the formation of these artists through the presentation of the curriculum of the painting course of the ENBA, the transcription of the its discipline plans and, mainly, of the the pressuposeds that guided the practical in it verified. We trace a panel of the artistic pensionate system kept in the Europe by the ENBA during the First Republic, understanding it as the logical complement of the artistic formation of the painters initiated in Brazil, from the transcription of the judgments relative to the so-called Travel Prizes (Prêmios de Viagem) and of a discution concerning the relations of the Brazilian painters with the artistic millieu of the main European cities frequented by them in the period (Munique, Rome and Paris). Finally, we display the systematic underlying the great stylistic variety that can be observed in the pictorial production of the artists of Rio de Janeiro in the First Republic, that direved directly from the diversity of subjects and/or functions played by its pictures.